Hardened body of slag and method for manufacturing the same
Patent Information
- Application Number
- CN202280036682.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2021-05-28
- Filing Date
- 2022-05-19
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2042-05-19
AI Technical Summary
[0004]然而,包含游离MgO的炼钢炉渣具有长期进行游离MgO的水合反应而发生膨胀的性质,因此,存在硬化体的膨胀裂缝的隐患,难以实现作为水合硬化体的材料的充分利用
[0025] According to the present invention, when using slag to manufacture a hardened body, even when using slag containing free MgO, such as steelmaking slag, as a material, expansion cracks caused by hydration expansion based on free MgO will not occur, and a hardened body can exhibit sufficient strength for its use as artificial stone in the early stages.
Smart Images

Figure BDA0004560264830000081 
Figure BDA0004560264830000091 
Figure BDA0004560264830000111
Abstract
Description
Technical Field
[0001] This invention relates to a hardened body manufactured using slag containing free MgO, such as steelmaking slag, as a material, and a method for manufacturing the hardened body. Background Technology
[0002] In the steelmaking process, to prevent MgO contained in refractory materials from dissolving into the slag during refining and causing refractory loss, MgO with a saturation solubility exceeding a certain level is sometimes added to the slag. The slag produced by such refining contains MgO remaining in an unreacted state from the refining process, as well as MgO that crystallizes during slag cooling. This unreacted MgO and crystallized MgO are referred to as free MgO.
[0003] As an attempt to fully utilize steelmaking slag, a hydrated hardened body of steelmaking slag has been used, for example, as disclosed in Patent Document 1. The hydrated hardened body described in Patent Document 1 comprises aggregate and binder material, which hardens upon the addition of water and mixing. The aggregate contains steelmaking slag containing unreacted CaO that has undergone a hydration reaction, and the binder material contains 50% by weight or more of a silica-containing substance with potential hydraulic properties and solidifies through a hydration reaction.
[0004] However, steelmaking slag containing free MgO has the property of expanding due to the long-term hydration reaction of free MgO. Therefore, there is a risk of expansion cracks in the hardened body, making it difficult to fully utilize it as a material for hydration hardening. Here, the hydration reaction of free MgO refers to the reaction in which free MgO in steelmaking slag comes into contact with moisture such as rainwater and seawater to form Mg(OH)2 (MgO + H2O → Mg(OH)2). Due to this reaction, the volume expands.
[0005] In the field of refractories, for example, the hydration inhibition technology of MgO by forming a crystalline film such as boric acid on the surface of a refractory, as disclosed in Patent Document 2, is known. Patent Document 2 discloses a method for preventing the disintegration of basic refractory bricks. This method includes forming a crystalline film of one or more of sulfate, boric acid, and borate on the surface of the basic refractory brick. The film is formed by immersing the basic refractory brick in an aqueous solution or by coating the basic refractory brick with the aqueous solution and then drying the aqueous solution. The aqueous solution is an aqueous solution in which the value of the mathematical expression 100c / (a×b) has a value of 0.2 or more and 1.0 or less, given that the weight of water is a (g), the saturated solubility is b (g), and the weight of the solute is c (g).
[0006] Existing technical documents
[0007] Patent documents
[0008] Patent Document 1: Japanese Patent No. 3582263
[0009] Patent Document 2: Japanese Patent Application Publication No. 8-169783 Summary of the Invention
[0010] The problem that the invention aims to solve
[0011] However, based on the aforementioned existing technology, an attempt was made to prepare a hardened body containing B2O3 to suppress the hydration expansion of free MgO, using steelmaking slag containing free MgO as aggregate, blast furnace slag powder, and ordinary silicate cement as an alkali-activating material. The result was that the body could not be deframed on the second day due to the setting delay effect of B2O3, and the 3-day compressive strength was less than 3 N / mm². 2 It cannot withstand use as a hardened material. Furthermore, it cannot suppress the hydration expansion of free MgO, resulting in cracks in the hardened material.
[0012] The present invention was made in view of the above circumstances, and its object is to provide a hardened body utilizing slag containing free MgO, such as steelmaking slag, which suppresses volume expansion caused by hydration reaction based on free MgO and increases strength in the early stage. In addition, a method for manufacturing the hardened body is also provided.
[0013] Problem Solving Methods
[0014] The main idea of the present invention for solving the above problems is as follows.
[0015] [1] A hardened body utilizing slag, wherein the slag contains free MgO,
[0016] In the aforementioned hardened body, the slag containing free MgO has a unit content of 2720 kg / m³. 3 The following unit weight of blast furnace slag powder is 250 kg / m³. 3 Above and 800kg / m 3 The following unit quantity of slaked lime is 12 kg / m³. 3 Above and 160kg / m 3 The following calculations use B2O3 as the unit amount for boron-containing substances, which is 0.5 kg / m³. 3 Above and 4.0 kg / m 3 the following.
[0017] [2] A method for manufacturing a hardened body using slag, wherein the method utilizes slag containing free MgO as a material, the method comprising:
[0018] The unit quantity of slag containing free MgO is set at 2720 kg / m³. 3Hereinafter, the unit quantity of blast furnace slag powder is set at 250 kg / m³. 3 Above and 800kg / m 3 Hereinafter, the unit quantity of slaked lime will be set at 12 kg / m³. 3 Above and 160kg / m 3 In the following calculations, the unit amount of boron-containing substances is set to 0.5 kg / m³ using B₂O₃ as the conversion factor. 3 Above and 4.0 kg / m 3 The following mixture is formed.
[0019] Water is added to the mixture, and the mixture is kneaded. Then, the kneaded mixture is allowed to solidify.
[0020] [3] A method for manufacturing a hardened body using slag, wherein the method utilizes slag containing free MgO as a material, the method comprising:
[0021] Slag containing free MgO is impregnated in a solution containing dissolved boron, or a solution containing dissolved boron is sprayed onto slag containing free MgO, so that boron-containing substances, calculated as B2O3, at least 0.10% by mass, are pre-adhered to the surface of the slag containing free MgO.
[0022] The unit weight of the above-mentioned slag containing free MgO, which is pre-attached with boron-containing substances, is set at 2720 kg / m³. 3 The following is an example of setting the amount of boron-containing material adhering to the surface of the slag to 0.5 kg / m³ (converted to B₂O₃). 3 Above and 4.0 kg / m 3 Hereinafter, the unit quantity of blast furnace slag powder is set at 250 kg / m³. 3 Above and 800kg / m 3 Hereinafter, the unit quantity of slaked lime will be set at 12 kg / m³. 3 Above and 160kg / m 3 The following mixture is formed.
[0023] Water is added to the mixture, and the mixture is kneaded. Then, the kneaded mixture is allowed to solidify.
[0024] The effects of the invention
[0025] According to the present invention, when using slag to manufacture a hardened body, even when using slag containing free MgO, such as steelmaking slag, as a material, expansion cracks caused by hydration expansion based on free MgO will not occur, and a hardened body can exhibit sufficient strength for its use as artificial stone in the early stages. Detailed Implementation
[0026] Hereinafter, an example of this embodiment will be described.
[0027] The hardened body utilizing slag in this embodiment (hereinafter also referred to as "slag hardened body") is manufactured by adding water to a mixture containing slag containing free MgO as a material, kneading it, and then allowing the kneaded mixture to solidify. In this hardened body, the unit amount of slag containing free MgO is 2720 kg / m³. 3 The following unit weight of blast furnace slag powder is 250 kg / m³. 3 Above and 800kg / m 3 The following unit quantity of slaked lime is 12 kg / m³. 3 Above and 160kg / m 3 The following calculations use B2O3 as the unit amount for boron-containing substances, which is 0.5 kg / m³. 3 Above and 4.0 kg / m 3 In this case, slag or natural aggregates free of free MgO may be used as materials, depending on the need. Slag free of free MgO refers to slag in which no periclase peak was confirmed by X-ray diffraction. Natural aggregates include, for example, "gravel and sand".
[0028] The slag hardened body of this embodiment is characterized in that, on average, per 1m 3 The hardened body contains 0.5 kg / m³ of B₂O₃. 3 Above and 4.0 kg / m 3 The following boron-containing substances are used. By adding boron-containing substances to slag containing free MgO, a crystalline film of boric acid or borate is formed on the surface of the free MgO in the slag. This crystalline film prevents the surface of the free MgO from contacting moisture in the gaseous atmosphere, such as the air. In other words, the crystalline film of boric acid or borate functions as a moisture-absorbing material, inhibiting the hydration of free MgO and preventing expansion cracks in the hardened slag body caused by the hydration expansion based on free MgO.
[0029] In the slag hardened body of this embodiment, the unit amount of boron-containing material used to suppress the hydration expansion of free MgO is set to 0.5 kg / m³ (converted to B₂O₃). 3 Above and 4.0 kg / m 3 The following is because the inventors discovered that the unit amount of boron-containing substances, converted to B2O3, is less than 0.5 kg / m³. 3 At that time, the effect of inhibiting hydration swelling was small; on the other hand, the concentration of B2O3 was greater than 4.0 kg / m³. 3 At that time, the hardened body will not solidify.
[0030] As a boron-containing substance, any substance in which boron is dissolved in water is acceptable, without any particular limitation. For example, boron trioxide (B2O3), boric acid (H3BO3), borax (Na2B4O5(OH)4·8H2O), and other boron oxides and boron compounds can be used.
[0031] Another feature of the slag hardened body of this embodiment is the use of hydrated lime (Ca(OH)2) as an alkali activating material. The reason for using hydrated lime is that: (1) it can suppress the expansion of free MgO in the slag hardened body without destroying the boric acid or borate crystal film on the surface of free MgO formed by boron-containing substances; (2) it can provide the alkali required to exhibit the potential hydraulic properties of blast furnace slag micro powder; and (3) it exhibits strength at an earlier stage compared to ordinary silicate cement.
[0032] It can be assumed that in the slag hardened body with added boron-containing substances, a magnesium borate-based crystalline film is formed on the surface of free MgO.
[0033] In the combination of blast furnace slag micropowder, commonly used as a binder material in slag hardening, and ordinary silicate cement, the pH (hydrogen ion concentration index) of the ordinary silicate cement is high, approximately 12.7. Therefore, the crystalline film of magnesium borate dissolves, reducing its effect on inhibiting the expansion of free MgO. On the other hand, the manifestation of the potential hydraulic properties of blast furnace slag micropowder requires the provision of an alkali. That is, for alkali-activated materials, it is required that the crystalline film formed by magnesium borate is not destroyed, and that an alkali is provided to exhibit the potential hydraulic properties of the blast furnace slag micropowder.
[0034] Therefore, in the slag hardened body of this embodiment, the pH of the saturated aqueous solution is 12.4, which is lower than the pH of silicate cement. Furthermore, hydrated lime, capable of providing alkali activation to blast furnace slag powder, is used as the alkali activation material. Additionally, when hydrated lime is used as the alkali activation material, strength is exhibited more quickly in the early stages compared to when ordinary silicate cement is used. From this perspective, it can be considered that using hydrated lime as the alkali activation material is appropriate.
[0035] In the slag hardening body of this embodiment, the hydrated lime in the slag hardening body is set at an average of 1m³ 3 12kg / m³ of hardened slag 3 Above and 160kg / m 3 The following is because the unit quantity of slaked lime is less than 12 kg / m³. 3 At that time, the paste ratio of water, blast furnace slag powder, and hydrated lime in the hardened body was insufficient, so the hardened body did not solidify. On the other hand, when the proportion of water, blast furnace slag powder, and hydrated lime in the hardened body is more than 160 kg / m³, the hardened body will not solidify. 3When slaked lime is used, the paste ratio in the hardened body becomes too high, and the strength does not improve. Therefore, the unit amount of slaked lime is set at 160 kg / m³. 3 the following.
[0036] In the slag hardened body of this embodiment, on average per 1m 3 Hardened slag body combined with blast furnace slag micro powder 250kg / m 3 Above and 800kg / m 3 The following is because, by limiting the unit amount of blast furnace slag powder to this range, the quantitative balance between the amount of alkali ions provided by slaked lime and the amount of reactive SiO2 in the blast furnace slag powder with potential hydraulicity becomes appropriate, and a hardened body with sufficient strength can be obtained.
[0037] The blast furnace slag powder used in manufacturing the hardened slag body of this embodiment is obtained by pulverizing blast furnace water-crushed slag. Preferably, the blast furnace slag powder has a particle size of about 0.1 mm or less and a specific surface area of about 3000 cm² based on Blaine's method. 2 / g or more. Additionally, if a specific surface area of 4000 cm² is used based on the Blaine method... 2 Blast furnace slag micro powder with a concentration of / g or higher has higher activity and is a further preferred option.
[0038] The slag containing free MgO used in manufacturing the slag-hardened body of this embodiment refers to slag in which periclase peaks are confirmed by X-ray diffraction. Slag generated during the smelting of high-chromium molten ferroalloys is particularly preferred. Examples of high-chromium molten ferroalloys include: chromium-containing molten pig iron, high-chromium molten steel (typically with a chromium content of 5% by mass or more, such as stainless steel), and chromium-containing master melts used to manufacture such high-chromium steel (e.g., molten ferroalloys smelted in an electric furnace or the like with a chromium concentration of 5% by mass or more and a carbon concentration of 1% by mass or more and less than 2% by mass).
[0039] For chromium-containing molten pig iron, smelting is typically carried out in electric arc furnaces, iron bath reduction furnaces, or vertical shaft reduction furnaces through the smelting and reduction of chromium ore. For high-chromium molten steel, smelting is carried out in primary refining furnaces such as electric arc furnaces, converters, and AOD furnaces, and secondary refining furnaces such as VOD furnaces, RH vacuum degassing devices, and ladle refining furnaces. In addition, the chromium-containing master melt used to manufacture high-chromium steel is mainly smelted in electric arc furnaces and converters.
[0040] In these smelting and refining furnaces, for molten reduction furnaces that moltenly reduce chromium ore, in order to protect the furnace refractory, an operation is performed to add MgO with a saturation solubility greater than that of the slag to the slag. Therefore, the resulting slag (chromium smelting slag) contains free MgO. Such slag is suitable for manufacturing the slag hardened body of this embodiment.
[0041] Although the free MgO content of the slag (referred to as "converter decarburization slag") produced when pure oxygen is supplied to the molten pig iron in the converter from top-blown lances or the like for decarburization refining of molten pig iron is lower than that of chromium smelting slag, it can still be used as slag containing free MgO when manufacturing the slag hardened body of this embodiment.
[0042] Furthermore, for the hardened slag body, strength is achieved by filling the gaps between aggregates such as slag with a paste-like component containing blast furnace slag powder, hydrated lime, and water, thereby achieving bonding. In the hardened slag body of this embodiment, the unit amount of slag containing free MgO is limited to 2720 kg / m³. 3 The following is because if the unit amount of slag containing free MgO exceeds 2720 kg / m³... 3 If the amount of blast furnace slag powder, hydrated lime, and water in the hardened body decreases, the bonding force of the aggregate decreases and the strength of the hardened body decreases.
[0043] On the other hand, in the slag hardening body of this embodiment, there is no lower limit on the unit amount of slag containing free MgO. This is because slag containing free MgO functions as aggregate in the slag hardening body, but slag without free MgO or natural aggregate can also be used as materials as needed. Therefore, it is not necessary to technically limit the lower limit on the unit amount of slag containing free MgO. However, if the unit amount of slag is too small, it is not conducive to the effective utilization of slag. Therefore, it is preferable to have an average of 1 m³ of slag containing free MgO. 3 The unit weight of slag containing free MgO in the hardened slag body is set at 300 kg / m³. 3 Therefore, slag containing free MgO can be effectively utilized.
[0044] Furthermore, in the slag hardened body of this embodiment, a high-performance water-reducing agent is preferably used. When manufacturing the slag hardened body, the strength of the slag hardened body can be increased by reducing the amount of water added during mixing. However, if the amount of water added during mixing is reduced, the material cannot be dispersed. The high-performance water-reducing agent is used to disperse the material while reducing the amount of water added. For example, a polycarboxylate-based high-performance water-reducing agent can be used. Generally, the amount of high-performance water-reducing agent used is preferably 0.3% by mass or more and 1.5% by mass or less, which is the sum of the unit amount of blast furnace slag powder and the unit amount of hydrated lime.
[0045] Next, the method for manufacturing the hardened slag body according to this embodiment will be described. There are two methods for manufacturing the hardened slag body according to this embodiment.
[0046] The method for manufacturing a slag hardened body is as follows: the unit amount of slag containing free MgO is set to 2720 kg / m³. 3 Hereinafter, the unit quantity of blast furnace slag powder is set at 250 kg / m³. 3 Above and 800kg / m 3 Hereinafter, the unit quantity of slaked lime will be set at 12 kg / m³. 3 Above and 160kg / m 3 In the following calculations, the unit amount of boron-containing substances is set to 0.5 kg / m³ using B₂O₃ as the conversion factor. 3 Above and 4.0 kg / m 3 Next, a mixture is formed, water is added to the mixture, and the mixture is kneaded. Then, the kneaded mixture is allowed to solidify.
[0047] In this case, slag or natural aggregates without free MgO can be used as materials, as needed. Additionally, an appropriate amount of high-performance water-reducing agent can be used.
[0048] Another method for manufacturing a hardened slag body is as follows: Slag containing free MgO is impregnated in a solution containing dissolved boron, or a mist of a solution containing dissolved boron is sprayed onto the slag containing free MgO, so that the boron-containing substance, calculated as B2O3, at least 0.10% by mass, is pre-adhered to the surface of the slag containing free MgO. Then, the unit weight of the slag containing free MgO pre-adhered with boron is set at 2720 kg / m³. 3 The following is an example of setting the amount of boron-containing material adhering to the surface of the slag to 0.5 kg / m³ (converted to B₂O₃). 3 Above and 4.0 kg / m 3 Hereinafter, the unit quantity of blast furnace slag powder is set at 250 kg / m³. 3 Above and 800kg / m 3Hereinafter, the unit quantity of slaked lime will be set at 12 kg / m³. 3 Above and 160kg / m 3 The mixture is then formed, water is added to the mixture, and the mixture is kneaded. The kneaded mixture is then solidified. The reason for pre-adhering boron-containing substances (equivalent to 0.10% by mass of B2O3) to the surface of the slag containing free MgO is that when the boron content (equivalent to 0.10% by mass of B2O3) is less than 0.10% by mass, the effect of inhibiting hydration expansion is insufficient.
[0049] In this case, slag or natural aggregates without free MgO can be used as materials, as needed. Additionally, an appropriate amount of high-performance water-reducing agent can be used.
[0050] As explained above, according to this embodiment, when manufacturing a slag hardened body, even when using slag containing free MgO, such as steelmaking slag, as the material, it is possible to obtain a hardened body that does not experience expansion cracks caused by hydration expansion based on free MgO and can exhibit sufficient strength for its use as artificial stone in the early stages.
[0051] Example 1
[0052] The embodiments of the present invention will be described below. In this embodiment, a hardened slag body was prepared using three types of slag (slag A to C) with the compositions shown in Table 1. It should be noted that in Table 1, "CaO / SiO2" represents the ratio of CaO concentration (mass%) to SiO2 concentration (mass%) in the slag (referred to as "basicity"), and "MgO" and "free MgO" represent the MgO concentration (mass%) and free MgO concentration (mass%) in the slag, respectively.
[0053] [Table 1]
[0054]
[0055] In the slag shown in Table 1, hardened bodies (examples of the present invention) were prepared by combining blast furnace slag powder, hydrated lime, natural aggregate (coarse aggregate), boron-containing substances, high-performance water-reducing agents, and water in unit quantities within the scope of the present invention. In the examples of the present invention, the unit quantity of boron-containing substances converted from B2O3 was set to 0.5 kg / m³. 3 1.0kg / m 3 2.0kg / m 3 3.5kg / m 3 4.0kg / m 3 For the unit amount of boron-containing substances converted from B2O3, the unit amount of slaked lime is set to 12 kg / m³. 3 15kg / m 344kg / m 3 59kg / m 3 100kg / m 3 144kg / m 3 160kg / m 3 .
[0056] In addition, for comparison, hardened bodies were also manufactured that did not contain hydrated lime but contained ordinary silicate cement, hardened bodies with the hydrated lime content set to a level outside the scope of this invention, hardened bodies without boron-containing substances, and hardened bodies with the boron-containing substance content converted from B2O3 set to 4.5 kg / m³. 3 Hardened body (comparative example).
[0057] In this embodiment, boron trioxide (B2O3) is used as a boron-containing substance and dissolved in water used to manufacture the hardened body.
[0058] For the hardened body, two types were manufactured: one for strength testing and the other for expansion assessment. For the hardened body used for strength testing, after solidification, it was removed from its frame and water-cured at 20°C for 3 days. The compressive strength was then measured based on JIS A 1108. Here, "age" refers to the number of days elapsed since the hardened body was cast from the slag. For the hardened body used for expansion assessment, after solidification, it was removed from its frame and water-cured at 20°C for 14 days. After curing, it was immersed in water at 80°C. The hardened body was observed 45 days after immersion to check for large cracks. The compressive strength was 3.0 N / mm². 2 The above are considered acceptable. Additionally, cases where the compressive strength cannot be measured due to failure to solidify after 3 days are indicated as "Unable to measure". In the expansion assessment, cases without identified cracks are considered "Acceptable", while cases with identified cracks are considered "Unacceptable". "Unable to measure" in both the compressive strength and expansion assessment columns indicates that the material has not solidified or has undergone hydration expansion without forming a hardened body.
[0059] Table 2 shows the fit table of the test specimens made using slag A, as well as the results of the compressive strength and expansion determination.
[0060] [Table 2]
[0061]
[0062] In Comparative Examples 1-3, which were made with ordinary Portland cement but without hydrated lime, the 3-day strength was less than 3.0 N / mm². 2 Similarly, in the expansion measurement, cracks were confirmed after 45 days, indicating that the free MgO had expanded.
[0063] In addition, the unit quantity of slaked lime is set at 6 kg / m³. 3In Comparative Examples 4-6, the test specimens did not solidify, and compressive strength and expansion could not be determined. In Comparative Examples 7-13 without added boron, cracks were detected after 45 days, confirming the expansion of free MgO. The unit amount of boron-containing material converted from B2O3 was set at 4.5 kg / m³. 3 In Comparative Examples 14-20, the test specimens did not solidify, so compressive strength and expansion could not be determined.
[0064] In contrast, it was confirmed that the unit quantity of slaked lime was set at 12 kg / m³. 3 Above and 160kg / m 3 The following uses a unit of measurement for boron-containing substances converted from B2O3, set at 0.5 kg / m³. 3 Above and 4.0 kg / m 3 In the following Examples 1 to 35 of the present invention, the 3-day compressive strength is 3.0 N / mm. 2 The above conditions were also found to be intact, with no cracks detected during the expansion assessment.
[0065] Table 3 shows the fit table of the test specimens made using slag B, as well as the results of the compressive strength and expansion determination.
[0066] [Table 3]
[0067]
[0068] In Comparative Examples 21-23, which were mixed with ordinary Portland cement but without hydrated lime, the 3-day strength was less than 3.0 N / mm². 2 In addition, the same situation was observed in the expansion measurement. After 45 days, cracks were confirmed, and it was confirmed that free MgO had expanded.
[0069] In addition, the unit quantity of slaked lime is set at 6 kg / m³. 3 In Comparative Examples 24-26, the hardened bodies did not solidify, and compressive strength and expansion could not be determined. In Comparative Examples 27-33 without added boron, cracks were detected after 45 days, and expansion of free MgO was confirmed. The unit amount of boron-containing material converted from B2O3 was set to 4.5 kg / m³. 3 In Comparative Examples 34-40, the hardened body did not solidify, and compressive strength and expansion could not be determined.
[0070] In contrast, it was confirmed that the unit quantity of slaked lime was set at 12 kg / m³. 3 Above and 160kg / m 3 The following uses a unit of measurement for boron-containing substances converted from B2O3, set at 0.5 kg / m³. 3 Above and 4.0 kg / m 3 In the following examples 36-70 of the present invention, the 3-day compressive strength is 3.0 N / mm.2 The above states are complete, and there is no breakage during the expansion determination.
[0071] Table 4 shows the fit table of the test specimens made using slag C, as well as the results of the compressive strength and expansion determination.
[0072] [Table 4]
[0073]
[0074] The unit quantity of slaked lime is set at 6 kg / m³. 3 The unit quantity of slag C is set to 3060 kg / m³. 3 In Comparative Examples 41-43, the hardened body did not solidify, and compressive strength and expansion could not be determined. In Comparative Examples 44-50 without added boron, cracks were detected after 45 days, and expansion of free MgO was confirmed. Furthermore, the unit amount of boron-containing material converted from B2O3 was set to 4.5 kg / m³. 3 In comparative examples 51-57, the hardened body did not solidify, and compressive strength and expansion could not be determined.
[0075] In contrast, it was confirmed that the unit quantity of slag C was set at 2720 kg / m³. 3 The following is an example of setting the unit quantity of slaked lime at 12 kg / m³. 3 Above and 160kg / m 3 The following calculations using B2O3 as the unit amount of boron-containing substances are set at 0.5 kg / m³. 3 Above and 4.0 kg / m 3 In Examples 71 to 105 of the present invention within the following range, the 3-day compressive strength is 3.0 N / mm. 2 The above states are complete, and there is no breakage during the expansion determination.
[0076] Example 2
[0077] The following experiment was conducted: Three types of slag (slag A to C) shown in Table 1 were brought into contact with a boron-containing substance. A hardened body was manufactured using slag with the boron-containing substance pre-adhered to its surface. Boron trioxide (B₂O₃) was used as the boron-containing substance. This boron trioxide reagent was dissolved in 50 times its mass of water to prepare an aqueous solution (boric acid solution). This aqueous solution was sprayed onto the slag in a mist, allowing the boron-containing substance (boric acid) to adhere to the slag surface. The slag was then dried and used as the material for the hardened body.
[0078] In slag pre-attached with boron-containing substances at a concentration of 0.10% or more (equivalent to B2O3), hardened bodies were prepared by mixing blast furnace slag powder, hydrated lime, natural aggregate (coarse aggregate), a high-performance water-reducing agent, and water in unit amounts within the scope of this invention (Examples of this invention). In these examples, the amount of boron-containing substances (equivalent to B2O3) attached to the slag was set to 0.1%, 0.3%, 0.5%, and 1.0% (equivalent to 1.0% of the slag mass). Furthermore, for comparison, hardened bodies with a boron-containing substance attachment amount outside the scope of this invention were also prepared (Comparative Examples).
[0079] In addition, two types of hardened bodies were manufactured: one for strength measurement and the other for expansion determination. The compressive strength and expansion determination of the manufactured hardened bodies were performed under the same conditions as in Example 1 above.
[0080] Table 5 shows the fit table of the test specimens made using slag A, as well as the results of the compressive strength and expansion determination.
[0081] [Table 5]
[0082]
[0083] It was confirmed that the unit quantity of slaked lime was set at 12 kg / m³. 3 Above and 160kg / m 3 The following is defined as follows: the boron-containing material adhering to the slag surface is calculated as B2O3, which is 0.10% or more of the slag. The amount of boron-containing material in the hardened body, calculated as the product of the unit amount of slag and the mass ratio of the adhering boron-containing material (calculated as B2O3), is the amount of boron-containing material in the hardened body (calculated as B2O3 in kg / m³). 3 = Unit weight of slag (kg / m³) 3 The mass ratio (mass%) of B2O3 converted from the amount of boron-containing substances adhered to it (%) / 100 is set to 0.5 kg / m³. 3 Above and 4.0 kg / m 3 In the following examples 106-125 of the present invention, the 3-day compressive strength is 3.0 N / mm. 2 Furthermore, even after being immersed in water at 80°C for 45 days, the hardened body remained intact.
[0084] On the other hand, in Comparative Examples 58-64, where the boron-containing material adhering to the slag surface was set at 0.05% by mass of the slag (converted to B2O3), the amount of boron-containing material in the hardened body, calculated based on the product of the unit amount of slag and the mass ratio of the adhering boron-containing material converted to B2O3, did not reach 0.5 kg / m³. 3In the expansion determination, a crack was confirmed after 45 days, indicating that the free MgO had expanded.
[0085] Table 6 shows the fit table of the test specimens made using slag B, as well as the results of the compressive strength and expansion determination.
[0086] [Table 6]
[0087]
[0088] It was confirmed that the unit quantity of slaked lime was set at 12 kg / m³. 3 Above and 160kg / m 3 The following definition assumes that the boron-containing material adhering to the slag surface, converted to B2O3, accounts for at least 0.10% of the slag by mass, and that the unit amount of boron-containing material converted to B2O3 in the hardened body, calculated based on the product of the unit amount of slag and the mass ratio of the adhering boron-containing material converted to B2O3, is 0.5 kg / m³. 3 Above and 4.0 kg / m 3 In the following examples 126-145 of the present invention, the 3-day compressive strength is 3.0 N / mm. 2 In conclusion, even after being immersed in water at 80°C for 45 days, the hardened body remained intact.
[0089] On the other hand, in Comparative Examples 65-71, where the boron-containing material adhering to the slag surface was calculated as 0.05% by mass of the slag (based on B2O3 conversion), the amount of boron-containing material in the hardened body, calculated based on the product of the unit amount of slag and the mass ratio of the adhering boron-containing material converted to B2O3, did not reach 0.5 kg / m³. 3 In the expansion determination, a crack was confirmed after 45 days, indicating that the free MgO had expanded.
[0090] The fit table of the test specimens made using slag C, as well as the results of the compressive strength and expansion determination, are shown in Table 7.
[0091] [Table 7]
[0092]
[0093] It was confirmed that the unit quantity of slaked lime was set at 12 kg / m³. 3 Above and 160kg / m 3 The following definition assumes that the boron-containing material adhering to the slag surface, converted to B2O3, accounts for at least 0.10% of the slag by mass, and that the unit amount of boron-containing material converted to B2O3 in the hardened body, calculated based on the product of the unit amount of slag and the mass ratio of the adhering boron-containing material converted to B2O3, is 0.5 kg / m³. 3 Above and 4.0 kg / m3 In the following examples 146-154 of the present invention, the 3-day compressive strength is 3.0 N / mm. 2 In conclusion, even after being immersed in water at 80°C for 45 days, the hardened body remained intact.
[0094] On the other hand, although the boron-containing material adhering to the slag surface accounts for more than 0.10% by mass of the slag when converted to B2O3, the amount of boron-containing material in the hardened body, calculated based on the product of the unit amount of slag and the mass ratio of the adhering boron-containing material converted to B2O3, exceeds 4.0 kg / m³. 3 In comparative examples 72-78, the test specimens did not solidify.
Claims
1. A hardened body utilizing slag, said slag containing free MgO, In the hardened body, the slag containing free MgO has a unit weight of 2720 kg / m³. 3 The following unit weight of blast furnace slag powder is 250 kg / m³. 3 Above and 800kg / m 3 The following unit quantity of slaked lime is 12 kg / m³. 3 Above and 160kg / m 3 The following calculations use B2O3 as the unit amount for boron-containing substances, which is 0.5 kg / m³. 3 Above and 4.0 kg / m 3 the following.
2. A method for manufacturing a hardened body using slag, wherein the method utilizes slag containing free MgO as a material, the method comprising: The unit quantity of slag containing free MgO is set at 2720 kg / m³. 3 Hereinafter, the unit quantity of blast furnace slag powder is set at 250 kg / m³. 3 Above and 800kg / m 3 Hereinafter, the unit quantity of slaked lime will be set at 12 kg / m³. 3 Above and 160kg / m 3 In the following calculations, the unit amount of boron-containing substances is set to 0.5 kg / m³ using B₂O₃ as the conversion factor. 3 Above and 4.0 kg / m 3 The following mixture is formed. Water is added to the mixture, and the mixture is kneaded. Then, the kneaded mixture is allowed to solidify.
3. A method for manufacturing a hardened body using slag, wherein the method utilizes slag containing free MgO as a material, the method comprising: Slag containing free MgO is impregnated in a solution containing dissolved boron, or a solution containing dissolved boron is sprayed onto slag containing free MgO, so that boron-containing substances, calculated as B2O3, at least 0.10% by mass of the slag, are pre-adhered to the surface of the slag containing free MgO. The unit quantity of the slag containing free MgO pre-attached with boron-containing substances is set at 2720 kg / m³. 3 The following is an example of setting the amount of boron-containing material adhering to the surface of the slag to 0.5 kg / m³ (converted to B₂O₃). 3 Above and 4.0 kg / m 3 Hereinafter, the unit quantity of blast furnace slag powder is set at 250 kg / m³. 3 Above and 800kg / m 3 Hereinafter, the unit quantity of slaked lime will be set at 12 kg / m³. 3 Above and 160kg / m 3 The following mixture is formed. Water is added to the mixture, and the mixture is kneaded. Then, the kneaded mixture is allowed to solidify.
Citation Information
Patent Citations
Method for preventing slaking of basic firebrick
JP1996169783A
Geopolymers and methods for their production
WO2005019130A1
Method for suppressing hydration of free mgo in slag, slag particles, slag particle production method, and artificial stone production method
WO2021065215A1